2021
DOI: 10.1126/sciadv.abk3283
|View full text |Cite
|
Sign up to set email alerts
|

The use of differential privacy for census data and its impact on redistricting: The case of the 2020 U.S. Census

Abstract: New Census privacy protections may introduce both bias and noise into redistricting and voting rights analysis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 33 publications
7
71
0
Order By: Relevance
“…Note that this result is supported by Kenny et al [5], which also predicts individual race and ethnicity, but additionally uses analysis of names to help predict race and ethnicity. Kenny et al found that TDA (using versions with more noise than the final version we tested) did not degrade the quality of these predictions.…”
Section: Our Simple Inference Non-attacksupporting
confidence: 66%
“…Note that this result is supported by Kenny et al [5], which also predicts individual race and ethnicity, but additionally uses analysis of names to help predict race and ethnicity. Kenny et al found that TDA (using versions with more noise than the final version we tested) did not degrade the quality of these predictions.…”
Section: Our Simple Inference Non-attacksupporting
confidence: 66%
“…For example, Kenny et al (2021) used the April 2021 version of the 2010 Census demonstration data to examine both the properties of these data for purposes of redistricting and to simulate alternative redistricting maps that conform to commonly used criteria for legally acceptable redistricting practices. They find systematic biases in these data along racial and partisan lines that reduce the heterogeneity by geography in both of these dimensions.…”
Section: Assessments Of 2010 Demonstration Data Products For Redistri...mentioning
confidence: 99%
“…Furthermore, Kenny et al (2021) examined the final version of the 2010 demonstration data released on August 12, 2021, that was produced using the version of the Census's TDA that formed the basis of the DAS for the 2020 Census redistricting data, including its greater privacy loss budget. These authors found that while this final demonstration product was an improvement over previous releases, it still produced biases in drawing and simulation of voting districts (VTDs).…”
Section: Assessments Of 2010 Demonstration Data Products For Redistri...mentioning
confidence: 99%
“…Quantitative geographers may be among the most impacted researchers, given their focus on aggregate geographic data, but the Census Bureau Disclosure Avoidance System and differential privacy are likely to have wide-reaching effects for non-quantitative researchers and policymakers, as well. Preliminary research has suggested that uncertainty may be much higher for certain places and groups, for example, indicating decadal population loss when none has occurred, for small towns and indigenous areas (Wezerek and Van Riper, 2020) or mis-characterizing population counts and characteristics in political redistricting (Kenny et al, 2021). In estimating possible effects on county-to-county migration data, Winkler et al (2021) find that uncertainty is potentially higher for Hispanic migrants, as well as the young and old.…”
Section: Uncertainty Is Dead; Long Live Uncertaintymentioning
confidence: 99%
“…3.As Kenny et al (2021) point out, the US Census Bureau has long adjusted data (e.g. record swapping) to help ensure confidentiality, however, the new Disclosure Avoidance System, which combines injecting noise into data with post-processing adjustments, is widely agreed to be an entirely different sort of confidentiality protection beast.…”
mentioning
confidence: 99%